2003
DOI: 10.1046/j.1420-9101.2003.00510.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatially structured genetic variation in a broadcast spawning bivalve: quantitative vs. molecular traits

Abstract: Understanding the origin, maintenance and significance of phenotypic variation is one of the central issues in evolutionary biology. An ongoing discussion focuses on the relative roles of isolation and selection as being at the heart of genetically based spatial variation. We address this issue in a representative of a taxon group in which isolation is unlikely: a marine broadcast spawning invertebrate. During the free-swimming larval phase, dispersal is potentially very large. For such taxa, small-scale popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(64 citation statements)
references
References 96 publications
7
56
1
Order By: Relevance
“…This result is consistent with previous reports of conspecific populations from the South China Sea and Sulu Sea reefs (Juinio-Meñez et al 2003), and contrasts with earlier population genetic studies of other tridacnid species, which revealed little genetic differentiation over broader geographic scales (reviewed by Juinio-Meñez et al 2003). Locus-specific heterozygote deficiencies (in this case GPI-1*) is a pattern frequently observed in bivalves (Luttikhuizen et al 2003 and references therein), and may be attributed to genotype scoring errors, as well as to biological/reproductive factors e.g. genetic differences between cohorts, differential selection, and subpopulation structure (Wahlund effect).…”
Section: Discussionsupporting
confidence: 87%
“…This result is consistent with previous reports of conspecific populations from the South China Sea and Sulu Sea reefs (Juinio-Meñez et al 2003), and contrasts with earlier population genetic studies of other tridacnid species, which revealed little genetic differentiation over broader geographic scales (reviewed by Juinio-Meñez et al 2003). Locus-specific heterozygote deficiencies (in this case GPI-1*) is a pattern frequently observed in bivalves (Luttikhuizen et al 2003 and references therein), and may be attributed to genotype scoring errors, as well as to biological/reproductive factors e.g. genetic differences between cohorts, differential selection, and subpopulation structure (Wahlund effect).…”
Section: Discussionsupporting
confidence: 87%
“…In addition, common garden experiments are also used to study the consequences of local adaptation for conservation (McKay et al, 2001) or even for ecosystem functioning (Bassar et al, 2010). Despite its name, and although it has been used extensively with plants (Linhart and Grant, 1996), this experimental approach can also be applied to a large variety of organisms including fish (Bassar et al, 2010;DeFaveri and Merilä, 2014), invertebrates (Spitze, 1993;Luttikhuizen et al, 2003) and small mammals (Bozinovic et al, 2009). The main limitations to this experimental design are the ability to breed the species and to grow the produced offspring in laboratory or seminatural conditions.…”
Section: Introductionmentioning
confidence: 99%
“…This led to the idea of testing selective divergence in quantitative traits by comparison of their population differentiation (Q ST ) with the population differentiation obtained from neutral molecular markers (F ST ) (Spitze, 1993). Three outcomes, each having a unique interpretation, are possible (Merila and Crnokrak, 2001): (i) Q ST 4F ST : this is commonly interpreted as evidence of divergent selection and adaptation to local environments (Podolsky and Holtsford, 1995;Bonnin et al, 1996;Latta and Mitton, 1997;Jaramillo-Correa et al, 2001;Steinger et al, 2002;Storz, 2002;Chan and Arcese, 2003;Luttikhuizen et al, 2003); (ii) Q ST and F ST do not differ: genetic drift alone is sufficient to explain the pattern of differentiation (Yang et al, 1996), although effects of natural selection and drift in certain cases can be indistinguishable in certain cases (Sokal and Wartenburg, 1983); and (iii) Q ST oF ST : convergent selection favoring the same phenotype in different environments is assumed (Kuittinen et al, 1997;Petit et al, 2001;Edmands and Harrison, 2003). However, interpretation of any discrepancy between Q ST and F ST as evidence of selection on a particular quantitative trait may not always hold.…”
Section: Introductionmentioning
confidence: 99%